BMP-2 impregnated biomimetic scaffolds successfully induce bone healing in a marginal mandibular defect - DeConde, Adam S. (2013)
EDUCATIONAL OBJECTIVE: To investigate the ability of an osteoconductive scaffold to heal a clinically common mandibular defect with BMP-2 in an animal model. OBJECTIVES: To test the osteoregenerative potential and dosing of bone morphogenetic protein-2 (BMP-2) impregnated biomimetic scaffolds in a rat model of a mandibular defect. STUDY DESIGN: Prospective study using an animal model. METHODS: Varied doses of BMP-2 (0.5, 1, 0.5 and 0.5 in microspheres, 5, 15 μg) were absorbed onto a biomimetic scaffold. Scaffolds were then implanted into marginal mandibular defects in rats. Blank scaffolds and unfilled defects were used as negative controls. Two months postoperatively, bone healing was analyzed with micro-computerized tomography (microCT). RESULTS: MicroCT analysis demonstrated all doses of BMP-2 induced successful healing of marginal mandibular defects in a rat mandible. Increasing doses of BMP-2 on the scaffolds produced increased tissue healing with 15 μg demonstrating significantly more healing than all other dosing (p < 0.01). CONCLUSIONS: BMP-2 impregnated biomimetic scaffolds successfully induce bone healing in a marginal mandibular defect in the rat. Percentage healing of defect, percentage of bone within healed tissue and total bone volume are all a function of BMP-2 dosing. There appears to be an optimal dose of 5 μg beyond which there is no increase in bone volume.